2008
DOI: 10.1007/s10578-008-0104-y
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically-Indexed and Self-Perceived Affective Empathy in Conduct-Disordered Children High and Low on Callous-Unemotional Traits

Abstract: Heart rate (HR) was employed to compare vicarious affective arousal across three groups of children (aged 7.6 - 11, N = 95): Conduct Disordered (CD) elevated on Callous-Unemotional traits (CD/CU), CD low on CU traits (CD-only), and [Symbol: see text]typically-developing' controls, matched in age, gender and socioeconomic background. While watching an emotion evocative film, participants' HR was monitored. Immediately after viewing, self-reported vicarious responses were obtained. Participants also completed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
105
3
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(117 citation statements)
references
References 55 publications
7
105
3
2
Order By: Relevance
“…At a neural level, adult criminal psychopaths (Decety, Skelly, & Kiehl, 2013) and children with high levels of callous-unemotional traits (Jones, Happe, Gilbert, Burnett, & Viding, 2010;Marsh et al, 2013) display reduced brain activity in empathy circuits (primarily anterior insula and anterior cingulate cortex) when viewing stimuli featuring others experiencing pain. Individuals with higher levels of psychopathy also show reduced psychophysiological arousal in response to others' distress (Anastassiou-Hadjicharalambous & Warden, 2008a;Blair, 1999;Blair, Jones, Clark, & Smith, 1997 1.3.1.3. Psychopathy and cognitive theory of mind.…”
Section: Reduced Outcome Aversion In Psychopathy and Utilitarian Moramentioning
confidence: 99%
“…At a neural level, adult criminal psychopaths (Decety, Skelly, & Kiehl, 2013) and children with high levels of callous-unemotional traits (Jones, Happe, Gilbert, Burnett, & Viding, 2010;Marsh et al, 2013) display reduced brain activity in empathy circuits (primarily anterior insula and anterior cingulate cortex) when viewing stimuli featuring others experiencing pain. Individuals with higher levels of psychopathy also show reduced psychophysiological arousal in response to others' distress (Anastassiou-Hadjicharalambous & Warden, 2008a;Blair, 1999;Blair, Jones, Clark, & Smith, 1997 1.3.1.3. Psychopathy and cognitive theory of mind.…”
Section: Reduced Outcome Aversion In Psychopathy and Utilitarian Moramentioning
confidence: 99%
“…Two studies were found that youths with both CD and higher CU traits showed a lower changing of heart rate to emotionally reminiscent ilms compared to youths with CD but without CU traits [132,133]. In addition, it was demonstrated that when anticipating aversive stimuli, skin conductance reactivity reduced in adolescents with psychopathic traits compared to controls [134,135].…”
Section: Other Biological Factorsmentioning
confidence: 99%
“…The presence of callous unemotional (CU) traits (e.g., lack of guilt and empathy, callous use of others) may be determining findings.CD children (n=33, age 7-11) with CU traits showed reduced basal HR and HR response to a scared boy, while no differences were found for CD children without CU traits (n=29) [1]. In two other studies HR response to film clips with sad people in DBD was investigated.Reduced HR response in DBD (n=22, age 8-12) was shown in one study [9], but no difference was found in the other study [16].…”
Section: Emotional Empathy In Conduct Disordermentioning
confidence: 99%